Kekurangcermatan Penulisan Kalimat dalam Karya Tulis Ilmiah Guru di Yogyakarta - Nanik Sumarsi (Kantor Bahasa Provinsi Maluku Utara, 2018)
This study aims to discuss inaccuracies of writing sentence in senior high school teacher’s scientific writing paper in Yogyakarta and correctness of error sentences that occur in the scientific paper. Principlly, this study is based on qualitative descriptive method. Data analysis is done with following steps. The first step is reading the KTIG (Teacher’s scientific writing paper) script and collecting error data (sentence error). Then, the next step is identifying types of errors, such as the buildup of ideas, ambiguity of sentences, redundancies, and illogical sentences. Once the data is identified, the next step is explaining why an error occurrs. The last step is giving correctness of sentence error. Based on the analyzed data, the lack of sentence writing accuracy in Teacher's scientific writing paper is caused by (1) the accumulation of ideas, (2) ambiguity of structure and ideas, (3) absence of main sentence, (4) superfluousness, (5) redundancy, illogical sentences, (7) sentence without predicate and dangling sentence, and (8) ineffectiveness due to pragmatic aspects.